Collective Action and Community Development : Evidence from Self-Help Groups in Rural India - Desai, Raj M.; Joshi, Shareen (Oxford University Press on behalf of the World Bank, 2016)
In response to the problems of high coordination costs among the poor, efforts are underway in many countries to organize the poor through “self-help groups” (SHGs)—membership-based organizations that aim to promote social cohesion through a mixture of education, access to finance, and linkages to wider development programs. We randomly selected villages in one of the poorest districts in rural India in which to establish SHGs for women. Two years of exposure to these programs increased women's participation in group savings programs as well as the non-agricultural labor force. Compared to women in control villages, treated women were also more likely to participate in household decisions and engage in civic activities. We find no evidence however, that participation increased income or had a disproportionate impact on women's socio-economic status. These results are important in light of the recent effort to expand official support to SHGs under India's National Rural Livelihood Mission.